Transcatheter occlusion of multiple pulmonary arterio venous malformations - Halkati Prabhu; Patted Suresh; Dixit M; Patil Ravikant (Wolters Kluwer Medknow Publications, 2010)
Pulmonary arterio venous malformations are one of the rare vascular anomalies. Usually single large pulmonary arteriovenous fistula (PAVF) can be closed through transcatheter route but multiple PAVF require surgical lobectomy. We describe a case of an 8-year-old boy with multiple PAVF, who underwent successful transcatheter closure with multiple coils.